PENGARUH PENGGUNAAN NON TUNAI DAN UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI PADA KABUPATEN/KOTA PROVINSI BALI - Dewi, I Gusti Ayu Agung Ade Tresya; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Economic growth in regencies / cities in Bali Province experienced fluctuations from 2015 to 2018. This growth was influenced by various supporting aspects, such as technological advances in finance, public consumption expenditure which fluctuated annually, and the minimum wage received by the community to meet the needs his life. The objective to be achieved is to analyze the effect of non-cash use, minimum wages and consumption expenditure either directly or not to economic growth. This study was sourced from secondary data, namely time series data, which began from 2015 to 2018 have 36 data, using path analysis techniques. The results of this study stated that 1) the use of non-cash and minimum wages had a positive and significant effect on community consumption expenditure in districts / cities in Bali Province. 2) minimum wages and public consumption expenditure have a positive and significant effect on economic growth in districts / cities in Bali Province. While the use of non-cash has a positive and not significant effect on economic growth in districts / cities in Bali Province. 3) public consumption expenditure mediates the effect of the use of non-cash and minimum wages on economic growth in districts / cities in Bali Province. Keywords : non-cash, minimum wage, consumption expenditure, and economic growth.